144k views
4 votes
Operations with Radical Expressions

Operations with Radical Expressions-example-1
Operations with Radical Expressions-example-1
Operations with Radical Expressions-example-2
Operations with Radical Expressions-example-3
Operations with Radical Expressions-example-4
Operations with Radical Expressions-example-5
User Kzrbill
by
5.7k points

1 Answer

5 votes

Answer:
30√(11)

Explanation:


3√(50) * √(22)

=
3√(5*5*2) * √(2*11)

=
3√(5*5*2*2*11)

=
3*5*2√(11)

=
30√(11)

******************************************

Answer:
6√(30)

Explanation:


√(20) * √(3) * √(18)

=
√(2*2*5) * √(3) * √(3*3*2)

=
√(2*2*5*3*3*3*2)

=
2*3√(5*3*2)

=
6√(30)

********************************************

Answer:
-√(5)

Explanation:


4√(20) - 3√(45)

=
4√(2*2*5) - 3√(3*3*5)

=
4*2√(5) - 3*3√(5)

=
8√(5) - 9√(5)

=
-√(5)

********************************************

Answer:
4√(5)

Explanation:


2√(5) + 3√(5) - √(5)

=
(2+3-1)√(5)

=
4√(5)

********************************************

Answer:
46√(2)

Explanation:


4√(32) + 6√(50)

=
4√(2*2*2*2*2) + 6√(2*5*5)

=
4*2*2√(2) + 6*5√(2)

=
16√(2) + 30√(2)

=
46√(2)





User Dave White
by
5.2k points